Ўзбекистон Республикасида етим болалар ва ота-она қарамоғидан маҳрум бўлган болалар таълимини қўллаб-қувватлашнинг қонуний асослари - Худайбергенова Дилором Зафаровна (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Abstract This article analyzes the legal, institutional and social mechanisms for supporting the education of orphans and children deprived of parental care in the Republic of Uzbekistan. Based on the current legislation and educational reforms, existing problems are identified and scientific and practical proposals are developed to eliminate them.